Prevalence of bloodstream pathogens is higher in neonatal encephalopathy cases vs. controls using a novel panel of real-time PCR assays. - Cally J Tann; Peter Nkurunziza; Margaret Nakakeeto; James Oweka; Jennifer J Kurinczuk; Jackson Were; Natasha Nyombi; Peter Hughes; Barbara A Willey; Alison M Elliott; Nicola J Robertson; Nigel Klein; et al. (PLoS ONE)
Background In neonatal encephalopathy (NE), infectious co-morbidity is difficult to diagnose accurately, but may increase the vulnerability of the developing brain to hypoxia-ischemia. We developed a novel panel of species-specific real-time PCR assays to identify bloodstream pathogens amongst newborns with and without NE in Uganda. Methodology Multiplex real-time PCR assays for important neonatal bloodstream pathogens (gram positive and gram negative bacteria, cytomegalovirus (CMV), herpes simplex virus(HSV) and P. falciparum) were performed on whole blood taken from 202 encephalopathic and 101 control infants. Automated blood culture (BACTEC) was performed for all cases and unwell controls. Principal findings Prevalence of pathogenic bacterial species amongst infants with NE was 3.6%, 6.9% and 8.9%, with culture, PCR and both tests in combination, respectively. More encephalopathic infants than controls had pathogenic bacterial species detected (8.9%vs2.0%, p = 0.028) using culture and PCR in combination. PCR detected bacteremia in 11 culture negative encephalopathic infants (3 Group B Streptococcus, 1 Group A Streptococcus, 1 Staphylococcus aureus and 6 Enterobacteriacae). Coagulase negative staphylococcus, frequently detected by PCR amongst case and control infants, was considered a contaminant. Prevalence of CMV, HSV and malaria amongst cases was low (1.5%, 0.5% and 0.5%, respectively). Conclusion/significance This real-time PCR panel detected more bacteremia than culture alone and provides a novel tool for detection of neonatal bloodstream pathogens that may be applied across a range of clinical situations and settings. Significantly more encephalopathic infants than controls had pathogenic bacterial species detected suggesting that infection may be an important risk factor for NE in this setting.